By Simulation Physics of Light by Rendering Software as Standard Render as of N-Enlargement Bounces from Glass Heart Object Get Similar Shape as Calabi Yau Variety Assumption - Golian, Peter (JOURNAL OF ADVANCES IN PHYSICS, 2020)
There are wave-particle properties of light. On photoreal visualization, we see only wave properties of light, photo from CAD scripts render, and where are particle properties? Similar as for example thermal analysis, but other, by simulating physics of light by standard rendering software of n- enlargement bounces could envoy particle properties, as from glass heart object get similar shape as Calabi Yau variety assumption.